Discovery of N-aryl sulphonamide-quinazoline derivatives as anti-gastric cancer agents in vitro and in vivo via activating the Hippo signalling pathway - Jin-Bo Niu; Chun-Hua Quan; Yuan Liu; Guang-Xi Yu; Jia-Jia Yang; Yin-Ru Li; Yan-Bing Zhang; Ying-Qiu Qi; Jian Song; Cheng-Yun Jin; Sai-Yang Zhang (Taylor & Francis Group, 2021)
Hippo signalling pathway plays a crucial role in tumorigenesis and cancer progression. In this work, we identified an N-aryl sulphonamide-quinazoline derivative, compound 9i as an anti-gastric cancer agent, which exhibited potent antiproliferative ability with IC50 values of 0.36 μM (MGC-803 cells), 0.70 μM (HCT-116 cells), 1.04 μM (PC-3 cells), and 0.81 μM (MCF-7 cells), respectively and inhibited YAP activity by the activation of p-LATS. Compound 9i was effective in suppressing MGC-803 xenograft tumour growth in nude mice without obvious toxicity and significantly down-regulated the expression of YAP in vivo. Compound 9i arrested cells in the G2/M phase, induced intrinsic apoptosis, and inhibited cell colony formation in MGC-803 and SGC-7901 cells. Therefore, compound 9i is to be reported as an anti-gastric cancer agent via activating the Hippo signalling pathway and might help foster a new strategy for the cancer treatment by activating the Hippo signalling pathway regulatory function to inhibit the activity of YAP.